Massive airway myiasis: an extreme rarity - Ming, Kai Teah; Yeen, Mei Chu; Sakuntala Dewi Shanmuganathan; Yeap, Boon Tat (BMA (United Kingdom), 2020)
Intubations are important live saving skills to maintain adequate ventilation and oxygenation. Common indications include impending upper airway obstruction, respiratory failure and impaired conscious level. Oral myiasis is an infrequently found disease which is characterised by ectoparasitic infestation of body tissues by fly maggots. We present a case report and share valuable experiences on a patient with massive airway myiasis causing upper airway obstruction which require emergency intubation.